Strategy of Goat Farming Improvement in Upland Watersheds - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: Goat farmiiig technologies improvement was studied in Gunungsari village